Expert knowledge elicitation with SHELF: introduction - O'Hagan, Anthony (Henry Stewart Talks, 2023)
Expert Knowledge Elicitation (EKE), Sheffield Elicitation Framework (SHELF), What is elicitation, Uncertainty, Experts and facilitators